Genetic analysis of egg production traits in four chicken breeds using a full diallel cross - Teshome, Philimon; Goshu, G.; Esatu, Wondmeneh; Dessie, Tadelle (Elsevier, 2025)
In the present study, effects of crossbreeding on egg production traits were evaluated using a 4 × 4 full diallel cross involving four chicken breeds: Improved Horro (H), Sasso (S), Potchefstroom Koekoek (K), and Dz-white feathered (D). The experiment included 800 chickens in a completely randomized design. Data on egg production traits were collected over 40 weeks (WK). Genotypes exhibited significant variations (P < 0.0001) in age at first egg (AFE), body weight at sexual maturity (BWSM), egg weight at first egg (EWAFE), egg number (EN), hen-housed egg production (HHEP), hen-day egg production (HDEP), and egg mass (EM). Heterosis effects (He) varied widely, with positive He for BWSM and EM in most crosses, while AFE consistently showed negative He. All reciprocal crosses showed positive He for EWAFE, while direct crosses had negative values except H × S and H × D. The K × H cross showed the highest He for HHEP (26.85%), HDEP (29.44%), EM (40.88%), and EN (28.27%). The cross D × H also exhibited strong He for HHEP (25.16%) and EN (24.60%), while K × S ranked second for HDEP (22.60%) and EM (33.89%). Reciprocal crosses showed positive He for BWSM, EWAFE, HHEP, HDEP, EM, and EN, except AFE. General combining ability (GCA) and specific combining ability (SCA) effects were highly significant (P<0.0001) for all traits. Reciprocal effects (RE) and maternal effects (Me) also influenced trait expression. GCA/SCA ratios indicated that non-additive effects influenced AFE, while additive effects influenced EWAFE. Moderate ratios for HHEP, HDEP, EM, and EN suggested a balance between additive and non-additive effects. Optimizing crossbreeding strategies, aligning with synthetic breed development, using a K sire with H and S dams, and a D sire with H dam, is recommended to improve egg production.